WORDS CONFUSE INDONESIAN LEARNERS (FALSE COGNATES) - Bire, Josua; Hambandima, Erny Selfina Nggala (Journal of Language, Education, Literature, and Culture, 2023)
This article entitled “Words confuse Indonesian learners” (false cognates) is written to help English teachers and students be aware that there might be confusion in their teaching and study. Data encountered in this writing are taken from reading a newspaper in NTT called TIMEX and TV news called METRO for one month from December 2022 to January 2023. The research results show that false cognates confuse Indonesian English learners 1. One meaning or single word but changed here and there, 2. Different substances, terms used in Indonesian context and meaning, 3. Acronyms that are not accustomed to English speakers, 4. Shorten words, which, when we refer back to English, have different meanings; 5: literary translation, 6. Word class changed, and 7. Words added